Allylmethylsulfide, a Sulfur Compound Derived from Garlic, Attenuates Isoproterenol-Induced Cardiac Hypertrophy in Rats - Mohammed, Soheb Anwar (Oxid Med Cell Longev, 2020)
Allylmethylsulfide (AMS) is a novel sulfur metabolite found in the garlic-fed serum of humans and animals. In the present study, we have observed that AMS is safe on chronic administration and has a potential antihypertrophic effect. Chronic administration of AMS for 30 days did not cause any significant differences in the body weight, electrocardiogram, food intake, serum biochemical parameters, and histopathology of vital organs. Single-dose pharmacokinetics of AMS suggests that AMS is rapidly metabolized into Allylmethylsulfoxide (AMSO) and Allylmethylsulfone (AMSO(2)). To evaluate the efficacy of AMS, cardiac hypertrophy was induced by subcutaneous implantation of ALZET® osmotic minipump containing isoproterenol (~5 mg/kg/day), cotreated with AMS (25 and 50 mg/kg/day) and enalapril (10 mg/kg/day) for 2 weeks. AMS and enalapril significantly reduced cardiac hypertrophy as studied by the heart weight to body weight ratio and mRNA expression of fetal genes (ANP and β-MHC). We have observed that TBARS, a parameter of lipid peroxidation, was reduced and the antioxidant enzymes (glutathione, catalase, and superoxide dismutase) were improved in the AMS and enalapril-cotreated hypertrophic hearts. The extracellular matrix (ECM) components such as matrix metalloproteinases (MMP2 and MMP9) were significantly upregulated in the diseased hearts; however, with the AMS and enalapril, it was preserved. Similarly, caspases 3, 7, and 9 were upregulated in hypertrophic hearts, and with the AMS and enalapril treatment, they were reduced. Further to corroborate this finding with in vitro data, we have checked the nuclear expression of caspase 3/7 in the H9c2 cells treated with isoproterenol and observed that AMS cotreatment reduced it significantly. Histopathological investigation of myocardium suggests AMS and enalapril treatment reduced fibrosis in hypertrophied hearts. Based on our experimental results, we conclude that AMS, an active metabolite of garlic, could reduce isoproterenol-induced cardiac hypertrophy by reducing oxidative stress, apoptosis, and stabilizing ECM components.